Phytotelmatrichis, a new genus of Acrotrichinae (Coleoptera: Ptiliidae) associated with the phytotelmata of Zingiberales plants in Peru - Darby, Michael; Chaboo, Caroline S. (Zootaxa, 2015)
Phytotelmatrichis, gen. n. a new genus of Ptiliidae: Acrotrichinae with two species Phytotelmatrichis peruviensis sp. n. and Phytotelmatrichis osopaddington sp. n. is described and illustrated. The new species were found during a survey of insects in the aquatic environments that form in the hollows (phytotelmata) in the leaves and floral bracts of Zingiberales plants. The new taxa were found in the the Zingiberales genera Calathea (Marantaceae), Heliconia (Heliconiaceae), and Alpinia and Renealmia (Zingiberaceae) in southern Peru. Sampling of other habitats in the same areas over five years and using a range of different techniques did not yield more specimens of this new genus. This suggests that the new species are restricted to phytotelmata.